Solve.
3d - 3 (d - 6) = 2 (d + 9)

3d - 3 (d - 6) = 2 (d + 9) 3d - 3d + 18 = 2d + 18 18 = 2d + 18 -2d = 18 - 18 -2d = 0 d = 0

Question

Asked 9/3/2010 5:38:34 PM

Updated 2/25/2014 12:55:23 PM

1 Answer/Comment

Rating

3

3d - 3 (d - 6) = 2 (d + 9)

3d - 3d + 18 = 2d + 18

18 = 2d + 18

-2d = 18 - 18

-2d = 0

d = 0

3d - 3d + 18 = 2d + 18

18 = 2d + 18

-2d = 18 - 18

-2d = 0

d = 0

Added 2/25/2014 12:55:23 PM

This answer has been confirmed as correct and helpful.

Solve: 4 - 9x = 29 - 4x **Weegy:** I'm sorry, i'm not good in math. (More)

Question

Expert Answered

Updated 2/26/2014 7:58:11 PM

1 Answer/Comment

4 - 9x = 29 - 4x

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

Added 2/26/2014 7:58:11 PM

This answer has been confirmed as correct and helpful.

Solve for x: 4 - 9x = 29 - 4x **Weegy:** 4 - 9x = 29 - 4x, -9x + 4x = 29 - 4,
-5x = 25,
x = 25/-5,
x = -5 **User:** Solve for x:
13 + 5x = 22 + 8x **Weegy:** 13 + 5x = 22 + 8x,
5x - 8x = 22 - 13,
-3x = 9,
x = 9/-3, x = -3 (More)

Question

Expert Answered

Updated 2/26/2014 8:00:08 PM

0 Answers/Comments

Solve.
5x + 5 (x - 3) = 15 **Weegy:** x=3 (which would make it 15 + 0 = 15) (More)

Question

Expert Answered

Updated 314 days ago|12/9/2017 5:04:01 AM

1 Answer/Comment

Solve.
10 - 5 (x - 5) = 4 (x - 1) **Weegy:** x= 39/9 (More)

Question

Expert Answered

Updated 6/17/2014 5:31:04 AM

1 Answer/Comment

27,515,534

questions answered

There are no comments.